Strategy for Strengthening Religious Moderation Among Minority Muslim Millennials: Policy Study at IAIN Sorong - Chudzaifah, Ibnu; Sukiman, Sukiman; Hikmah, Afroh Nailil; Toyibah, Nur (Arfannur, 2024)
This study aims to explore the role of the State Islamic Institute (IAIN) Sorong in strengthening religious moderation in Muslim minority areas, especially in Southwest Papua. As the only State Islamic Religious College in this region, IAIN Sorong has a strategic position in grounding the values of religious moderation, which is supported by the high index of religious harmony in the region (78.63 percent). This study uses a descriptive qualitative research method to describe in detail how religious moderation is understood, implemented, and promoted in the academic environment of IAIN Sorong. The results show that IAIN Sorong implements religious moderation through various programs and activities that prioritize the values of national commitment, tolerance, anti-violence, and accommodation of local culture. These programs include interfaith dialogues, seminars, multicultural courses, and cultural festivals, which create an inclusive and harmonious campus atmosphere. The strategy of religious moderation at IAIN Sorong involves a comprehensive approach in education, extracurricular activities, and community service, which is also supported by the Center for Religious Moderation Studies. With a strong national commitment, IAIN Sorong strives to create a peaceful campus environment and become an example in building a moderate, tolerant, and peace-loving society. This study confirms the important role of IAIN Sorong in overseeing religious moderation in Southwest Papua.